Pengaruh Kepemimpinan Otokrasi Terhadap Kinerja Karyawan Dengan Motivasi Intrisik Sebagai Variabel Moderator (Studi Kasus Pada Badan Pendidikan Dan Pelatihan Badiklat Provinsi Bandar Lampung) - Sugeng; Jati Imantoro; Rio Septian (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the effect of autocratic leadership on employee performance with intrinsic motivation as a moderator variable. This research is quantitative, where quantitative research is research that uses data types that can be measured or calculated directly through measuring research variables using numbers. The data analysis technique used is the analytical method which includes instrument requirements testing, analysis requirements testing and Moderated Regression Analysis (MRA) testing. The results of the study show that autocratic leadership has no effect on the performance of the Badiklat Education and Training Agency in Bandar Lampung Province. Intrinsic motivation has a positive and significant effect on autocratic leadership on employee performance at the Badiklat Education and Training Agency in Bandar Lampung Province. Keywords: Autocratic Leadership, Employee Performance, Intrinsic Motivation